THE U.K. APPLIES TO JOIN THE CPTPP: WHAT ARE THE IMPLICATIONS FOR CANADA? - Hugh Stephens (The School of Public Policy Publications, 2021)
The U.K’s request to join the Comprehensive and Progressive Trans-Pacific Partnership (CPTPP) could be a tremendous boon for this bloc. The CPTPP has 11 members at present, including Canada. However, four members — Peru, Chile, Malaysia and Brunei — have yet to complete the ratification process. The U.K.’s potential accession could lead the CPTPP to develop further in response to renewed interest from present and prospective members. Canada and the U.K. have already been discussing interim trading arrangements in the form of the Trade Continuity Agreement (TCA), which replaces existing rules designed when the U.K. was still a member of the European Union. Both countries have committed to reaching a new, permanent bilateral agreement by 2024. If the U.K. joins the CPTPP, Canada will thus end up negotiating two trade agreements with the same country at the same time. Canada is unlikely to win additional access to the U.K. market beyond what it enjoys through the TCA. At the same time, Canada is unlikely to grant the U.K. additional access to protected sectors through the CPTPP. But this doesn’t mean that Canada has nothing to gain from the U.K. joining the CPTPP. The addition of a substantial economy like the U.K. to the CPTPP could prompt the four foot-dragging members to complete ratification. Without that, they will have no say in the negotiations over the U.K.’s accession or the outcome. The U.K.’s experience could also encourage non-members like South Korea and Taiwan to take the plunge and apply to join the pact. The United States was an original member of the CPTPP’s precursor, the Trans-Pacific Partnership, but pulled out during the Trump administration. The U.K’s entry may not be enough to convince the new government to change course and so far, the Biden administration has not signalled that accession is a priority. Still, the U.K.’s admission has the potential to expand the trading bloc and Canada should make the most of this. It does require the careful adjustment of any potential Canadian concessions granted as part of the CPTPP accession negotiations against the need for leverage in future bilateral trade negotiations with the U.K. But this balancing act shouldn’t prevent Canada from supporting the U.K.’s request to join the CPTPP. The opportunities and rewards over the long term are too substantial for any other decision.